Examining Public Preferences for the Allocation of Resources to Rehabilitative Versus Punitive Crime Policies. (July 2015) - Baker, Thomas; Falco Metcalfe, Christi; Berenblum, Tamar; Aviv, Gali; Gertz, Marc
Fear of crime has been recognized as one of the driving forces underlying the punitive turn in the criminal justice system. Despite this, evidence suggests that rehabilitative efforts are still supported by the general public. The current study uses a national random sample to examine the impact of fear on public preference for allocating resources to rehabilitative versus punitive criminal justice system policies. Contrary to prior studies, respondents are forced to make a choice between punitive and rehabilitative options, and both the emotional and cognitive aspects of crime salience—fear of crime and victimization risk—are evaluated to determine their independent and combined impact on crime policy preference. The findings suggest that the majority of the public prefers putting resources toward rehabilitative crime polices, but fear of crime and risk of victimization both reduce this tendency. The implications of our results for current criminal justice system policies are discussed.